New species in the sap beetle genus Soronia Erichson (Coleoptera: Nitidulidae: Nitidulinae) from China - Chen, Xiaoxiao; Huang, Min (Zootaxa, 2021)
Three new species of sap beetles in the genus Soronia Erichson (S. expansa sp. nov., S. magnipunctura sp. nov. and S. xiangxiyuanica sp. nov.) are described and photographed. Two newly recorded species from China, S. gratiosa Kirejtshuk, 1988 and S. grisea (Linnaeus, 1758), are photographed and this new range extension is documented. A key to species of the genus Soronia in China is provided.